Большая Российская энциклопедия: в 30 т . - Кравец С.Л. (Большая Рос. энцикл., 2007)
Экземпляры: 3ф., 10,11, 14, 16, 15ф, чз. (17.10.07г.) / Инвентарный номер: 43505 / Цена: / Сис.шифр: 92 / Авт.знак: Б79 / ББК: 92